E-Government Untuk Peningkatan Tata Kelola Informasi dan Pelayanan Desa Jagalempeni - Warjiyono .; Husni Faqih - AMIK BSI TEGAL (Universitas Bina Sarana Informatika, 2017)
Abstract- This study aims to meet the needs of dissemination and acceptance of information from the Government of Jagalempeni Village as a state servant to the community of Jagalempeni Village. Currently information and services are carried out conventionally based on working hours, face-to-face so that services are limited, information is not extensive, potential areas are less well known, reports of unfree and less privileged citizens. Village website is needed for information more quickly, accurate conveyed, more maximal service and the existence of transparency of information and data. For that researchers will build an E-Government in the form of Village website with the concept of information, integration, interaction and service as a medium for improving governance of information and public services Jagalempeni Village to a good village (Good Governance).Keywords: e-Government, Governance, Jagalempeni Village Abstract- Penelitian ini bertujuan untuk memenuhi kebutuhan penyebaran dan penerimaan informasi dari Pemerintah Desa Jagalempeni selaku abdi negara kepada masyarakat Desa Jagalempeni. Saat ini informasi dan pelayanan dilakukan secara konvensional berdasarkan jam kerja, face-to-face sehingga pelayanan terbatas, informasi tidak luas, potensi daerah kurang dikenal luas, laporan warga tidak bebas dan kurang prifasi. Website Desa sangatlah diperlukan agar informasi lebih cepat, akurat tersampaikan, pelayanan lebih maksimal dan adanya transparansi informasi dan data. Untuk itu peneliti akan membangun sebuah E-Government dalam bentuk website Desa dengan konsep informasi, integrasi, interaksi dan pelayanan sebagai media untuk peningkatan tata kelola informasi dan pelayanan publik Desa Jagalempeni menuju Desa yang baik (Good Governance).Keywords : e-Government, Tata Kelola, Desa Jagalempeni